Sejarah Ilmu Dakwah - Hasnawirda Hasnawirda (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
The history of Islamic preaching science is Islamic preaching process began from dimensions of meaning of Islamic preaching words from the classical era until now. Because the Islamic preaching word are difference with praying, fasting, pilgrimage and the like, who have limited understanding by the Prophet Muhammad saw. So this writing will load giving meaning of Islamic preaching  word in beginning of the history, giving meaning of Islamic preaching of clssic era, giving meaning of Islamic preaching  of modern era, and the history of Islamic preaching in all of Instituteof Islamic religiousstate  in Indonesia. The history of Islamic preaching science is Islamic preaching process began from dimensions of meaning of Islamic preaching words from the classical era until now. Because the Islamic preaching word are difference with praying, fasting, pilgrimage and the like, who have limited understanding by the Prophet Muhammad saw. So this writing will load giving meaning of Islamic preaching  word in beginning of the history, giving meaning of Islamic preaching of clssic era, giving meaning of Islamic preaching  of modern era, and the history of Islamic preaching in all of Instituteof Islamic religiousstate  in Indonesia. Key word: dakwah, ilmu dakwah